A walking intervention for sedentary employees: effects on self-regulation and self-efficacy - Rodríguez-Hernández, Mynor G. (Escuela de Educación Física y Deportes - Universidad de Costa Rica, 2020)
A 10-week walking intervention was designed to examine how physical activity affects self-regulation and self-efficacy in sedentary employees. The intervention was completed by 68 participants randomly assigned to three groups: intermittent walking, continuous walking, or control. Self-regulation, self-efficacy and walking behavior were measured at baseline, week-6, and week-11. Walking activity significantly (p<.05) increased for the continuous walking group from baseline to week-6 (p=.033), the percentage of change was significantly higher compared to the control group from baseline to week-11 (p=0.042). Significant improvements on self-regulation were observed with the continuous group from baseline to week-6 and week-11 (p<0.05). However, self-efficacy decreased from baseline to week-6 (p=.047) and week-11 (p=.008) for all groups. Sedentary employees may benefit more from a continuous walking program due to enhanced self-regulatory skills. Intermittent walking activity may be also a feasible approach to reduce sedentary behavior, however more research is needed to test whether or not sedentary employees can meet daily physical activity recommendations. It is also important to review in future research, the link between physical activity and self-efficacy.